Heterogeneity of rock-hosted microbial communities in a serpentinizing aquifer of the Coast Range Ophiolite - Twing, Katrina I.; Brazelton, William J.; McCollom, Tom M.; Schubotz, Florence; Pendleton, H. Lizethe; Harris, Rachel L.; Brown, Annemarie R.; Richins, Seth M.; Kubo, Michael D. Y.; Hoehler, Tori M.; Cardace, Dawn; Schrenk, Matthew O. (Frontiers in Microbiology, 2025)
The movement of groundwater through fractured bedrock provides favorable conditions for subsurface microbial life, characterized by constrained flow pathways and distinctive local environmental conditions. In this study, we examined a subsurface microbial ecosystem associated with serpentinized rocks recovered from the Coast Range Ophiolite in northern California, USA. The distribution and diversity of microbial communities at various depths within two separate cores reaching up to 45 m below the land surface were investigated with microbiological and geochemical approaches. Core samples contained low total organic carbon content, low DNA yields, and low copy numbers of 16S rRNA genes, yet some samples still yielded amplifiable DNA sequences. The microbial community composition of rock cores was distinct from groundwater, and source tracking of DNA sequences indicated that groundwater is not a significant source of DNA into basement rocks. In contrast, the microbial community of some rock core samples shared similarities with overlying soil samples, which could indicate potential contamination, weathering of shallow serpentinites, or a combination of both. Individual DNA sequences of archaea and bacteria predicted to be endemic to the basement rocks were identified by differential abundance analyses. Core-enriched sequences were distinct from those in groundwater or in the overlying soils and included OTUs related to Serpentinimonas as well as putatively anaerobic, deep subsurface-associated taxa such as methanogens and Bathyarchaeia. Stable isotope analyses of organic and inorganic carbon did not reveal a chemoautotrophic signal and were instead consistent with a primarily surface vegetation source of organic carbon into the basement. This census of archaeal and bacterial DNA sequences associated with altered ultramafic rocks provides a useful resource for further research into the potential for deep subsurface microbial activity fueled by geochemical reactions associated with serpentinization.